2005
DOI: 10.1007/s10350-005-0120-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Diagnosis and Treatment of Rectal Cancer on Paid and Unpaid Labor

Abstract: Diagnosis and treatment of rectal cancer affect paid and unpaid labor. The impact on paid labor is most pronounced. Multiple other sociodemographic and quality of life-related variables also were associated with paid labor. Patient information and decision making on preoperative radiotherapy should include the effects on paid labor, and interventions focused on promoting paid labor participation in patients with rectal cancer should be tailored to the specific characteristics and needs of those patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 29 publications
1
32
0
1
Order By: Relevance
“…This has in part been seen also in other studies [16,18,19,26,38,39]. The findings are not unexpected due to the nature of the diseases: These illnesses may be quite debilitating, thus influencing both work abilities and possibilities.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This has in part been seen also in other studies [16,18,19,26,38,39]. The findings are not unexpected due to the nature of the diseases: These illnesses may be quite debilitating, thus influencing both work abilities and possibilities.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have suggested that any effect of cancer will be more severe in persons who perform manual, strenuous labor and have inflexible work schedules [21, 23, 29,38]. This type of labor is most common among persons with lower education.…”
Section: Education As a Modifying Factormentioning
confidence: 99%
“…() found an earlier return to work as age increased, whereas Van den Brink et al . (), Bouknight et al . () and Spelten et al .…”
Section: Resultsmentioning
confidence: 95%
“…Lower education was associated with less or later return to work (Van den Brink et al . ), a negative influence on return to work up to 5 years after diagnosis (Eaker et al . ), and a decreased chance of employment for both men and women (Taskila‐Brandt et al .…”
Section: Resultsmentioning
confidence: 99%
“…This likely confirms that having more children generates more unpaid work. None of the factors associated with unpaid work in POISE were modifiable, unlike factors associated with return to paid employment for young stroke survivors (independence in ADL at 28 days after stroke) [6] or people with rheumatoid arthritis and rectal cancer [13,28]. As a marker of recovery, participation in unpaid work after stroke may be less influenced by socio-demographic and treatment-related factors because unpaid work is a necessity and can be taken up at the patient's own pace and time in keeping with their capabilities [28].…”
Section: Discussionmentioning
confidence: 99%